Development of a scaled doubly-fed induction generator for assessment of wind power integration issues - Dehnavifard, Hossein (Department of Electrical Engineering, 2017)
Years of experience have been dedicated to the advancement of thermal power plant technology, and in the last decade the investigation has focused on the wind energy conversion system (WECS). Wind energy will play an important role in the future of the energy market, due to the changing climate and the fossil fuel crisis. Initially, wind energy was intended to cover a small portion of the energy market, but in the long term it should compete with conventional fossil fuel power generation. The movement of the power system towards this new phenomena has to be investigated before the wind energy share increases in the network. Therefore, the wind energy integration issues serve as an interesting topic for authors to improve the perception of integration, distribution, variability and power flow issues. Several simulation models have been introduced in order to resolve this issue, however, the variety in types of wind turbines and the network policies result in these models having limited accuracy or being developed for specific issues. The micro-machine is introduced in order to overcome the challenges of simulation models and the costs involved in field tests. In the past, the grid integration issue of large turbo-alternators was solved by the micro-machines. A variety of tests are possible with the micro-machines and they also increase the flexibility of the system. The increased accuracy as well as the ability to carry out real-time analysis and compare actual field test data are strengths worth utilizing. This project involves the designing and the prototyping of a scaled doubly-fed induction generator (micro-DFIG). The machine is also analysed and tested. The scaling of the micro-machine is achieved by means of a dimensional analysis, which is a mathematical method that allows machines and systems to be downscaled by establishing laws of similitude between the reference model and its scaled model. MATLAB/SIMULINK, Maxwell and Solid Work are employed to achieve the objectives of this project.